Integration of Islamic Law and Banjarese Customary Law of Inheritance System Tionghoa Muslim Community in Banjarmasin, South Kalimantan - Muzainah, Gusti; Mansyuroh, Firqah Annajiyah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The Tionghoa Muslim community is part of the life of the nation and state as a whole, one of the many ethnicities that are the features of the social identity of the archipelago. The history of the development of Islam and Tionghoa in Banjarmasin has an affiliation. This study aims to determine how the distribution of Tionghoa ethnic Muslim heritage in Banjarmasin. The method used is empirical legal research/field research, and the approach used in the sociology of law approach. The results of this study indicate the existence of legal integration. The pattern of behavior in the distribution of inheritance of Tionghoa descendants who are Muslim in Banjarmasin basically contains three main divisions of inheritance, namely through traditional heir deliberation, not dividing the inheritance, and dividing through the provisions of Islamic inheritance law. The use of inheritance law for Tionghoa Muslims in Banjarmasin is not fully subject to Islamic inheritance law, even though the inheritance law that applies to them is Islamic inheritance law. This happens because of the diversity of religions that exist in a family so that they put forward the principles of harmony and kinship so that there are no disputes.